About the Influence of SiO2 on the Temperature Behaviour of Ruthenate Based Thick Film Resistors. (1987) - Storbeck, I.; Wolf, M.
Abstract : Substituting glass by SiO2 in thick film resistors results in a small increase of R□, a decrease of dR□ /dT and an increase of d 2 R□ /dT 2 (at room temperature). From these experimental results it follows that substituting glass by SiO2 leads to an increase in the resistance of the tunnel barrier, determining the resistivity of the TFRs. The other microscopic quantities, like charging energy andHTC ρ of ruthenate, are estimated using the model of Pike and Seager, the generalization of Which (necessary in order to take into account the influence of the strain dependence of R□ and R□ (T) in a correct way) is derived.